The Effect of the Evoking Freedom Technique on Compliance with a Server's Suggestion: An Evaluation in a Restaurant. (June 2017) - Guéguen, Nicolas; Jacob, Céline; Pascual, Alexandre
The evoking freedom technique is a verbal compliance technique that consists of soliciting someone to comply with a request by simply saying that the solicitee is free to accept or refuse the request. The effect of this technique on customer behavior has never been tested, however. When presenting the menu to a patron, a waitress was instructed to suggest a dish. In half of the cases, when making this suggestion, the employee added that the patron was free to choose a different dish. Results showed that compared to a control condition, the suggestion associated with the evoking freedom technique had a positive effect on the patron's choice. The magnitude and the generalization of this technique are discussed.